2014
DOI: 10.1177/1049909114527338
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Centered Care or Cultural Competence

Abstract: The literature about Chinese attitudes toward death and dying contains frequent references to strong taboos against open discussion about death; consequently, there is an assumption that dying at home is not the preferred option. This focused ethnographic study examined the palliative home care experiences of 4 Chinese immigrants with terminal cancer, their family caregivers, and home care nurses and key informant interviews with 11 health care providers. Three main themes emerged: (1) the many facets of taboo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…25,41,43,51 Sixteen studies conceptualized advance care planning as a process of conversations about personal preferences. 24,25,38,39,41–44,4651,53,54 Cultural identity ( n = 11) and cultural value ( n = 10) were the most-frequently studied elements of acculturation. Methodological quality was categorized as being strong in seven studies, good in eight, adequate in three, and low in three (Supplemental Tables 2 and 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…25,41,43,51 Sixteen studies conceptualized advance care planning as a process of conversations about personal preferences. 24,25,38,39,41–44,4651,53,54 Cultural identity ( n = 11) and cultural value ( n = 10) were the most-frequently studied elements of acculturation. Methodological quality was categorized as being strong in seven studies, good in eight, adequate in three, and low in three (Supplemental Tables 2 and 3).…”
Section: Resultsmentioning
confidence: 99%
“…According to some Chinese immigrants, children agreeing to and supporting parents’ wishes to withhold or withdraw life-sustaining treatments may be considered not being filial. 4749,53…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 ] Without appropriate training, healthcare providers may not feel confident about negotiating the balance between patient-centered care and cultural competency, especially related to psychosocial needs that are considered culturally sensitive. [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of researchers have reported that culture could affect personal health habits and behavior, along with the cognition of, and seeking a response to healthy behavior [11–13]. Accordingly, Nielsen et al [14], conducted a qualitative study which showed that the issue of death is often considered a taboo when discussed in public for the Chinese. From this point of view, because nurses are the contemporary healthcare providers, and place a significant role in performing cultural assessments, they must be sensitive to the delivery of culturally appropriate care [13, 15].…”
Section: Introductionmentioning
confidence: 99%